Technical analysis gives you courage, but not money-von the relationship between technical analisys usage, overconfidence and investment performance - Kubińska, Elżbieta; Czupryna, Marcin; Markiewicz, Łukasz; Czekaj, Jan (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2018)
This paper investigates the psychological background of the use of technical analysis in the financial markets. Such a background may give additional explanations to the popularity and common usage of technical analysis as an investment decision tool. This popularity is puzzling due to the missing theoretical and scientific background of technical analysis and the contradictory empirical evidence on its effectiveness. We postulate that overconfidence (regardless of its manifestation: calibration, better than average, and illusion of control) reinforces technical analysis usage. This hypothesis is tested in the present study conducted with professionals (traders in a proprietary trading company) and novices (finance students). The hypothesis received partial empirical support. Overconfidence – in particular the illusion of control – explains technical analysis usage in both investigated groups
Argumenta Oeconomica, 2018, Nr 1 (40), s. 317-344
Keywords: overconfidence; calibration effect; illusion of control; better than average; technical analysis